A Longitudinal Study of Herd Behavior in the Adoption and Continued Use of Technology1 - Sun, Heshan (MIS Quarterly, 2013)
Herd literature suggests that people tend to discount their own beliefs and imitate others when making adoption decisions and that the resulting adoption decisions are fragile and can be easily reversed during the post-adoptive stage. This helps explain why the adoption of a number of new technologies―from Amazon’s Kindle, to Apple’s iPod, iPhone, and iPad, to various types of Web 2. 0 technologies―appears to have adoption patterns similar to those of new fashion trends (i. e., an initial en masse acquisition followed by subsequent abandonment). It is important to understand these phenomena because they are strongly related to the staying power of technology. From a herd behavior perspective, this study proposes two new concepts, namely discounting one’s own information and imitating others, to describe herd behavior in technology adoption. A research model is developed to describe the conditions under which herd behavior in technology adoption occurs, how it impacts technology adoption decision making, and how it influences post-adoptive system use. A longitudinal study is conducted to examine the research model. Findings from this research suggest that the discounting of one’s own beliefs and the imitating of others when adopting a new technology are provoked primarily by the observation of prior adoptions and perceptions of uncertainty regarding the adoption of new technology. Herd behavior has a significant influence on user technology adoption; however, it does not necessarily lead to the collapse of the user base, as predicted in the herd literature. Instead, imitation can help reduce post-adoption regret and thus serve as a legitimate strategy for choosing a good enough technology, which may or may not be the best option to enhance job performance. People tend to adjust their beliefs when herding and also to revive their discounted initial beliefs to modify their beliefs about the technology at the post-adoptive stage. Findings from this study have significant research and practical implications.